PREVALENCE OF PERIODONTITIS IN DIABETIC AND NON-DIABETIC PATIENTS - Thaper, Shamit; Thaper, Tanvi; V, Vishnu Priya; Thaper, Rajeev; Thaper, Reena (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Periodontitis is a chronic inflammatory condition characterized by destruction of periodontal tissues and resulting in loss of connective tissue attachment, loss of alveolar bone, and formation of pathological pockets around the diseased tooth. Diabetic patients are more prone to periodontal diseases as they are more susceptible to infections. Studies have proved that periodontitis can be considered as a complication of diabetes. Method: A total of 50 individuals will be surveyed in this study. 25 patients aged 40-60 years with diabetes and 25 non-diabetic controls in good general health aged 40-60 years. All subjects will be given clinical periodontal exam for probing depth, attachment loss, bleeding on probing, the presence of plaque and calculus, and alveolar bone loss. Expected Outcome: Increase in periodontitis is expected to be seen in the diabetic patients as compared to the non-diabetic group. Thus, periodontitis is expected to be considered as a complication of diabetes. Result: The result showed that diabetes is a significant risk factor in diabetes. Conclusion: Increase in periodontitis is expected to be seen in the diabetic patients as compared to the non - diabetic group. Thus, periodontitis is expected to be considered as a complication of diabetes. Keywords: Periodontitis, diabetes, probing depth, plaque, calculus Â 